Analysis Of Quality In Solid State Welding (Copper-Copper) By Using NDT And DT By Altering Physical Properties At Constant Time. (2017) - Siva kishore babu, K.; Koteswararao, B.; Suresh, Y.; Ravi, D.
Abstract: In this work we analyzed the diffusion welding of similar material copper-copper by keeping time as constant and by varying the physical properties such as temperature and pressure. So that the welded pieces undergone for further analysis such as mechanical properties at the welded areas. We used both destructive 2 and non destructive testing methods. The bonding 1 is done at different temperatures such as 700°C, 750°C and 800°C and also pressure varies 5MPa, 10MPa and 15Mpa respectively. After joint made in bonding machine the entire zone of working area where bonding was done is allowed to cooling for 6 to 8 hours. In EDM machine 3 the welded joints cut as per as our requirements to perform both DT and NDT 4 methods. Out of all the results obtained the bonded pieces which are bonded at 750°C, 10MPa for 90 minutes gives the optimum bonding strength.